Understanding the Profile, Motivations and Current Status of Academic Graduates through Open and Distance Schooling in India - Jyotsna Jha; Neha Ghatak; Shreekanth Mahendiran (Journal of Learning for Development, 2017)
In India, Open and Distance Learning for secondary and higher secondary level is mainly provided by the National Institute of Open Schooling (NIOS). Secondary education in India pertains to class 9 and 10 catering to the age group of 15 to 16. Similarly, higher secondary education refers to class 11 and 12 catering to the age group of 17 to 18. Based on research supported by the Commonwealth of Learning (COL) this paper discusses the results from a telephone survey of close to 1000 learners who were enrolled with NIOS and completed secondary and higher secondary education during 2008-2012 in selected states. It emerged that nearly 81 per cent of respondents were gainfully employed and NIOS helped them look for better jobs, widen their job search, and gain more stable (permanent) and secure (government) jobs. NIOS has successfully enabled a good proportion of learners to continue with their higher education. Flexibility offered by open schooling is the main motivation to join NIOS; individuals facing various constraints in accessing regular secondary education have opted for this option. It appears that two different kinds of learners join NIOS at these two levels; the secondary level seems to have a bigger representation from lower socio-economic strata. The role of open schooling in reducing the gender gap at secondary level of schooling remains mixed.